PENGARUH INSENTIF TERHADAP PRESTASI KERJA (STUDI PADA KARYAWAN BAGIAN PENJUALAN DEALER SEPEDA MOTOR MEREK HONDA PT. MITRA PINASTHIKA MUSTIKA MOTOR PEKANBARU) - Teguh Prasetyo; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was condudted in PT. Mitra Pinasthika Mustika Motor Pekanbaru. The setting of this problem is the influence the granting of incentives to job performance the department of marketing at PT. Mitra Pinasthika Mustika Motor Pekanbaru. The purpose of this research is to know the granting of incetives, job performance, and know how the granting of incentives to job performance the department of marketing at PT. Mitra Pinasthika Mustika Motor Pekanbaru.The author uses descriptive quantitative methods of analisys. Data collection using the questionnaire. The sample used is the census. Data sources used are primary data or data obtained directly from the object of research, secondary data and data collected or the outhor of the PT. Mitra Pinasthika Mustika Motor Pekanbaru.The result of this research shown that the granting of incetives influence significant of job performance the department of marketing at PT. Mitra Pinasthika Mustika Motor Pekanbaru.Keywords: Granting of incentives, job performace, employee on department of marketing